2019
DOI: 10.15388/problemos.95.12
|View full text |Cite
|
Sign up to set email alerts
|

Design Science Research for Computational Thinking in Constructionist Education: A Pragmatist Perspective

Abstract: [full article, abstract in English; abstract in Lithuanian] The article examines the modern computer-based educational environment and the requirements of the possible cognitive interface that enables the learner’s cognitive grounding by incorporating abductive reasoning into the educational process. Although the main emphasis is on cognitive and physiological aspects, the practical tools for enabling computational thinking in a modern constructionist educational environment are discussed. The presented analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
0
6
0
1
Order By: Relevance
“…Finally, for educational foundations, we consider problem‐ and project‐based approaches, not only from the perspectives of instructional design, but also, and what is particularly important in the context of our study, from constructionists' and pragmatists' perspective of STEM education [13]. Constructionism provides foundations for important practical settings, considering education as a meaningful and socially connected activity.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, for educational foundations, we consider problem‐ and project‐based approaches, not only from the perspectives of instructional design, but also, and what is particularly important in the context of our study, from constructionists' and pragmatists' perspective of STEM education [13]. Constructionism provides foundations for important practical settings, considering education as a meaningful and socially connected activity.…”
Section: Discussionmentioning
confidence: 99%
“…Araujo et al (2019) analyzed the answers of 1564 students who participated in the Bebras challenge from statistical perspective, and their findings showed that the Bebras questions were effective in measuring students' CT concepts and skills. Dolgopolovas et al (2015) also found that Bebras questions were effective in measuring students' understanding of CT and used the results as a basis for adjusting lectures. Indeed, the level of CT skills measured by the Bebras CT Challenge questions is the degree to which students can apply CT skills to solve real-world problems (Izu et al, 2017).…”
Section: Evaluation Of Ctmentioning
confidence: 95%
“…Although Scratch has primarily been associated with a young learning audience (e.g., Chou, 2020;Rose et al, 2020), it's a user-friendly visual interface where students stack and fit blocks together, rather than write code via complex and technical syntax. This block-building metaphor for programming and coding, however, can encourage CT for beginners in the domain regardless of age (e.g., Dolgopolovas et al, 2015;Korkmaz, 2016;Romero et al, 2017). With Scratch, users can learn the ISSN 2513-8359 fundamental principles of programming (e.g., sequences, loops, conditional statements, etc.)…”
Section: What Is Scratch Programming/coding?mentioning
confidence: 99%